PENGARUH SUSTAINABILITY REPORT TERHADAP KEMUNGKINAN TERJADINYA FINANCIAL DISTRESS DENGAN COMPANY PERFORMANCE SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2012-2017 - Levina Audrey; Synthia Madya Kusumawati (Universitas Multimedia Nusantara, 2019)
The aim of this study is to analyze the effect of sustainability report on the possibility of financial distress with company perfomance as the mediation variable in manufacturing companies listed in the Indonesia Stock Exchange within the period of 2012 to 2017. The number of sample companies that fit the established criteria are as many as 12 companies, with the total sustainability reports reported during 2012 to 2017 as many as 53 samples. The analytical method used in this study is multiple regression and logistic regression analysis. The results of the study, first sustainability report has a significant influence on company performance only from the economic aspects and product responsibilities aspect. Second, financial performance which proxy by return on assets does not have significant influence on the possibility of financial distress. Third, sustainability report does not have influence in predicting the possibility of financial distress.